THE LIFE BEFORE ADAM: Al-ṬABATABA’IS PERSPECTIVE IN Al-MIZAN - Abdul Hakim Wahid; Iqbal Afif (ILMU USHULUDDIN, 2025)
This study aims to explore life on Earth before Adam was sent down to it. It employs a qualitative method with a focus on thematic analysis from the perspective of al-Ṭabāṭabā'ī as presented in his tafsir work, al-Mīzān fī Tafsīr al-Qur’ān. According to the Iranian exegete, the dialogue between the Angels and Allah recorded in Surah al-Baqarah verse 30 indicates the existence of living beings on Earth before the creation of Adam. His interpretation of Surah Fuṣṣilat verse 25, al-Nūr verse 45, and al-Nisā’ verse 1 reveals the beings that were present prior to Adam’s descent, namely jinn, animals, and prehistoric humans categorized within the hominidae family. By applying the grounded theory approach, this study finds that al-Ṭabāṭabā'ī rejects the theory of macroevolution of the human body, as reflected in his interpretation of the phrase nafs wāḥidah in Surah al-Nisā’ verse 1. There, he affirms that all humans originated from this one soul, which he identifies as Adam and Eve. In other words, humans today do not have a genealogical connection with any ancient humans, and therefore have never undergone significant changes in their bodies because since Adam, the first human created, he was already in the most perfect physical condition.